High polyhydroxybutyrate production in Pseudomonas extremaustralis is associated with differential expression of horizontally acquired and core genome polyhydroxyalkanoate synthase genes - Catone, Mariela V. (2014)
Fil: Catone, Mariela V. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Química Biológica. Buenos Aires, Argentina.